2014
DOI: 10.3109/10799893.2014.919592
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D receptorBsmIgene polymorphism with the risk of type 2 diabetes mellitus

Abstract: Relationship between vitamin D receptor (VDR) BsmI (rs1544410) gene polymorphism and the type 2 diabetes mellitus (T2DM) susceptibility is still conflicting at present. This meta-analysis was conducted to assess the association between VDR BsmI gene polymorphism and the risk of T2DM. The association studies were identified from PubMed, and Cochrane Library on 1 January 2014, and eligible investigations were included and synthesized using meta-analysis method. Eleven reports were recruited into this meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
2
13
0
1
Order By: Relevance
“…Data of the present study showed that vitamin D status was significantly associated with HbA1c after adjusting for sex, age, BMI, and duration of diabetes. Data of this work correlates with another study in South Korea which explained the negative relationship between vitamin D status and glycemic control in existing T2DM, which reached a similar conclusion [29]. In addition, evidence from a number of studies has suggested a relationship between vitamin D and micro-vascular complications of T2DM.…”
Section: Resultssupporting
confidence: 87%
“…Data of the present study showed that vitamin D status was significantly associated with HbA1c after adjusting for sex, age, BMI, and duration of diabetes. Data of this work correlates with another study in South Korea which explained the negative relationship between vitamin D status and glycemic control in existing T2DM, which reached a similar conclusion [29]. In addition, evidence from a number of studies has suggested a relationship between vitamin D and micro-vascular complications of T2DM.…”
Section: Resultssupporting
confidence: 87%
“…Regarding (Taq1, Bsm1) genotypes and alleles distribution we didn’t find significant statistical differences between patients with T2DM and controls. Similarly other previous studies [23] , [24] , [26] and a Meta analysis done on 11 reports [28] did not find any significant differences regarding VDR BsmI genotypes among T2DM and controls, also Turkish investigators didn’t find association between Taq1 polymorphism and T2DM [29] .…”
Section: Discussionmentioning
confidence: 52%
“…The role of VDR gene polymorphism and type 2 diabetes has been studied, but the results are not consistent among different populations. Regarding VDR BsmI gene polymorphism, two recent meta-analysis studies did not find an association with type 2 diabetes risk in Asian or Caucasian populations [ 36 , 37 ]. Heterogeneity among populations and the lack of studies to elucidate the genetic differences might explain the discrepancies between the studies [ 16 ].…”
Section: Discussionmentioning
confidence: 99%